1998
DOI: 10.1006/jmsc.1997.0236
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the spatial structure and biomass evaluation ofNephrops norvegicus(L.) populations in the northwestern Mediterranean by geostatistics

Abstract: The spatial distribution and biomass of Nephrops norvegicus were assessed by trawling over commercial fishing grounds (''Serola'', off Barcelona, Spain) during two surveys (spring and fall 1991), using geostatistical methods. The surveys were set 6 months apart, in order to analyse possible seasonal differences. In the present surveys, Norway lobster was caught between 200 and 600 m depth, with peak abundance at about 400 m. The analysis of the structure of spatial correlation by means of semivariograms showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 8 publications
0
45
0
Order By: Relevance
“…Maynou et al (1996) showed that depth-related zonation of decapod crustaceans is complemented by a significant horizontal component that reflects a strong two-dimensional spatial heterogeneity. Abundant species like Pandalidae and Aristeidae shrimps and N. norvegicus (Abelló et al, 1988norvegicus (Abelló et al, , 2002Cartes and Sardà 1993;Maynou and Sardà 1997;Maynou et al, 1998; have a patchy distribution related to geomorphology (e.g. canyons), sediment re-suspensions and other factors that may increase local production and food availability (Cartes and Sardà, 1993;Cartes, 1994;Maynou et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Maynou et al (1996) showed that depth-related zonation of decapod crustaceans is complemented by a significant horizontal component that reflects a strong two-dimensional spatial heterogeneity. Abundant species like Pandalidae and Aristeidae shrimps and N. norvegicus (Abelló et al, 1988norvegicus (Abelló et al, , 2002Cartes and Sardà 1993;Maynou and Sardà 1997;Maynou et al, 1998; have a patchy distribution related to geomorphology (e.g. canyons), sediment re-suspensions and other factors that may increase local production and food availability (Cartes and Sardà, 1993;Cartes, 1994;Maynou et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…This is of utmost importance, because there is a huge amount of spatial dependence of biotic responses that has previously been ignored or erroneously addressed through the use of traditional statistics that assume independence between observations (Liebhold & Gurevitch 2002). In marine populations, this approach has been undertaken for modeling spatial structure of populations (Pelletier & Parma 1994, Maravelias et al 1996, estimating biomass or abundance (Simard et al 1992, Petitgas 1993, Maynou et al 1998, Gutiérrez & Defeo 2003, identifying cohorts in space (Roa & Tapia 2000) and evaluating sampling designs (Defeo & Rueda 2002), mainly in the open sea and in continental shelf waters. However, estuarine species (resident and transient) have received less attention concerning structure of ecological patterns and processes, with only some research recently documented on fish populations (Rueda 2001, Rueda & Defeo 2001, 2003a.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this patchy distribution, data from marine abundance surveys are highly skewed and have a large variance, and the sample mean has a low level of precision even for relatively intense surveys (Pennington and Godø, 1995). Also, Maynou et al (1996Maynou et al ( , 1998) demonstrated a highly patched distribution for crustaceans in the Mediterranean. In this sea a multiespecific fishery exists (Farrugio et al, 1993), and the differences observed between hauls may be due to the aggregation pattern of the species or to their day-night behaviour along the water column.…”
Section: Discussionmentioning
confidence: 99%
“…The trawl used in this experience is the common commercial trawl net used in the region (Catalan coast), with a headrope of 25 m and a total length of 27 m (see Sardà et al, 1998 for further details). The trawl net was operated with a pair of flat, rectangular, iron otter boards measuring 1.20 x 2 m and weighing 400 kg with bridles of 75 m. Scanmar remote control measures give a mean of 13.5 m of horizontal opening and 1.9 m of vertical opening.…”
Section: The Gearmentioning
confidence: 99%